Farmer Empowerment Strategies Through Organic Vegetables Development - Maulida Murdayanti; Jabal Tarik Ibrahim; Istis Baroh (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Organic vegetable cultivation system is a system for growing vegetables that is safe for consumption. The aims of this study were to conduct external and internal analysis of Mulyo Santoso Farmers Group Association using SWOT analysis, to find out effective strategies in empowering farmers through vegetable development, and to compile strategies for empowering farmers through organic vegetable development by Mulyo Santoso Farmers Group Association. This study is a descriptive study using quantitative descriptive approach. The data used were primary data obtained through interviews using questionnaires. This research used SWOT analysis method. The sampling technique used was census, using all members of the population as samples. Internal factor analysis results show the acquisition of a strength indicator score of 1.53 and a weak indicator score of 1.04. The results of the analysis on external factors acquisition show the opportunity indicator score of 1.32 and the threat indicator score of 1.20. The resulting value of SWOT diagram analysis on the X axis for internal factors is 0.49 and Y axis on external factors is 0.12. Based on the results of the SWOT analysis, it is known that the strategy used by Mulyo Santoso Farmers Group Association is an aggressive or progressive strategy, by using the power to take advantage of opportunities by creating, producing and developing businesses of processed agricultural products, such as processed chips and catering services of healthy foods, as well as adding more varieties of cultivated vegetables and sell organic fertilizer to supplement the income